Learning from other Domains to Advance AI Evaluation and Testing: Medical Device Testing: Regulatory Requirements, Evolution and Lessons for AI Governance - Aboy, Mateo; Minssen, Timo (2025)
The field of medical devices exemplifies the transformative potential of technology in addressing healthcare challenges. Testing in the medical device domain is intricately tied to regulatory requirements across jurisdictions. During the pre-market phase, medical testing establishes baseline safety and effectiveness metrics through bench testing, performance standards, and clinical studies. Post market testing ensures that real-world data informs ongoing compliance and safety improvements. Testing is indispensable in translating technological innovation into safe and effective medical devices. The regulation of medical devices plays a foundational role in safeguarding public health by ensuring that devices are safe, effective, and high-quality. In the global marketplace, the United States, the UK Medicines and Healthcare Products Regulatory Agency (MHRA), and the European Union represent some of the most influential regulatory jurisdictions, each with comprehensive frameworks: the U.S. Food and Drug Administration (FDA) medical device regulations, the MHRA (MDD) and European Union Medical Device Regulation (EU MDR). While there are country-specific differences with regards to the particular pre-market and post-market review procedures, most developed jurisdictions regulate medical devices similarly to the US or European models.